Exosomes and osteosarcoma drug resistance - Fu, Huichao; Wu, Yunjiao; Chen, Jianbai; Hu, Xing; Wang, Xiaoyan; Xu, Gongping (Frontiers in Oncology, 2023)
Osteosarcoma(OS) is a primary malignant tumor of bone characterized by the formation of bone tissue or immature bone by tumor cells. Because of its multi-drug resistance, even with the improvement of chemotherapy and the use of targeted drugs, the survival rate of osteosarcoma(OS) is still less than 60%, and it is easy to metastasize, which is a difficulty for many clinicians and researchers. In recent years, with the continuous research on exosomes, it has been found that exosomes play a role in the diagnosis, treatment and chemotherapy resistance of osteosarcoma due to their unique properties. Exosomes can reduce the intracellular accumulation of chemotherapeutic drugs by mediating drug efflux, thus inducing chemotherapeutic resistance in OS cells. Exosomal goods (including miRNA and functional proteins) carried by exosomes also show great potential in affecting the drug resistance of OS. In addition, miRNA carried by exosomes and exosomes exist widely in tumor cells and can reflect the characteristics of parent cells, so it can also be used as a biomarker of OS. At the same time, the development of nanomedicine has given a new hope for the treatment of OS. Exosomes are regarded as good natural nano-carriers by researchers because of their excellent targeted transport capacity and low toxicity, which will play an important role in the field of OS therapy in the future. This paper reviews the internal relationship between exosomes and OS chemotherapy resistance, discusses the broad prospects of exosomes in the field of diagnosis and treatment of OS, and puts forward some suggestions for the study of the mechanism of OS chemotherapy resistance.